Implementation of the Cooperative Learning Model Type TSTS Assisted by Concrete Media to Improve Mathematics Learning Outcomes - Krisnawati; Nur Haizah Aopmonaim; Waode Ekadayanti (Jurnal Wawasan Sarjana, 2025)
This study was conducted to improve the learning outcomes of second-grade students in mathematics at SD IT Rumah Anak Soleh Buton. The research applied classroom action research carried out in two cycles. Each cycle consisted of the stages of planning, implementation, observation, and reflection. The learning process was designed by applying the Cooperative Learning Model type Two Stay Two Stray, assisted by concrete media, to make mathematical concepts more accessible and meaningful for students. Data collection techniques included observation sheets, test instruments, and documentation, which were analyzed descriptively to capture both the process and the results of student learning. The findings of the study revealed that student learning outcomes improved across the cycles. Initially, many students had difficulty achieving the expected mastery in addition and subtraction, but after the implementation of the model, a significant improvement was observed. The cooperative approach encouraged active participation, peer learning, and better conceptual understanding. The use of concrete media also helped students relate abstract mathematical ideas to real-life contexts, thus strengthening their comprehension and motivation. Based on these results, it can be concluded that the Cooperative Learning Model type Two Stay Two Stray with concrete media is effective in improving mathematics learning outcomes among second-grade students.